2018
DOI: 10.2176/nmccrj.cr.2017-0230
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Development of Encapsulated Subdural Hematoma in the Posterior Cranial Fossa after Cardiac Surgery: A Case Report

Abstract: We report a case of an encapsulated subdural hematoma in the posterior cranial fossa, showing spontaneous development and rapid increase in size after cardiac surgery. An 86-year-old woman underwent aortic valve replacement for aortic valve stenosis, followed by anticoagulant therapy with heparin. Three days after the cardiac surgery, she complained of headache. Computed tomography revealed development of a subdural hematoma in the posterior cranial fossa. The hematoma rapidly increased in size within 7 days. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…However, since the number of reports is limited, the optimal treatment is unknown. [ 4 ] In the present case, considering that the patient was in use of anticoagulant therapy, a less invasive burr hole surgery was indicated to reduce the risk of postoperative bleeding and we had an excellent outcome with complete resolution of symptoms and postoperative CT demonstrating resolution of the pathology.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…However, since the number of reports is limited, the optimal treatment is unknown. [ 4 ] In the present case, considering that the patient was in use of anticoagulant therapy, a less invasive burr hole surgery was indicated to reduce the risk of postoperative bleeding and we had an excellent outcome with complete resolution of symptoms and postoperative CT demonstrating resolution of the pathology.…”
Section: Discussionmentioning
confidence: 83%
“…In some cases, no cause is found. [ 4 ] Furthermore, a CSH could be the result of a transformation of an acute one. The predominant manifestations are headaches, vomiting, cerebellar symptoms, and cranial nerve dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Kochi et al have reviewed rare cases of spontaneous posterior fossa CSDH and reported that 12 out of the 13 cases (92.3%) were female patients. 21 ) The reason for female predominance is unclear, but sexual anatomical features and/or vascular differences might exist in the posterior fossa.…”
Section: Discussionmentioning
confidence: 99%